Teknik Membaca Al-Quran Melalui Drilling Dan Pembiasaan (Studi Kasus di MI Al-Irsyad Al-Islamiyyah) - Husnul Khotimah (Edudeena : Journal of Islamic Religious Education, 2021)
Abstract: The main purpose of this research is to find out how the process of implementing learning techniques to read the Qur'an. It has been proven effective and efficient for grade 1 students of MI Al-Irsyad Al-Islamiyyah and the extent of progress after the learning techniques are implemented. This study uses a descriptive qualitative approach and the type of case study research and data analysis techniques Miles and Huberman, researchers are able to provide research results including: (1) learning techniques used are drilling and habituating techniques ; (2) this technique has proven to be effective and efficient when used in learning to read the Qur'an which is based on Ivan Pavlov's classical conditioning theory and Pierre S. Bourdeun's Habitus Theory; (3) the visible results are an increase in the percentage of students' competence in reading the Qur'an from 55 to 93 percent and are able to achieve the learning target, namely when the class increases they are able to complete the volume of iqro and are able to read the Qur'an in accordance with tajwid which exists; (4) other results in the form of additional competencies such as being able to memorize short letters in juz amma starting from QS. An-Nas to QS. Al-Qari'ah, Asmaul Husna and reading dzikir after prayer smoothly. This is a very good achievement considering that 90 percent of student input when they were students of MI Al-Irsyad Al-Islamiyyah had not been able to recite the dzikir reading. Abstrak: Tujuan utama dari penelitian ini adalah untuk menemukan teknik pembelajaran membaca al-Quran bagi anak-anak. Hal ini sangat terbukti efektif dan efisien untuk diterapkan pada siswa kelas 1 MI al-Irsyad al-Islamiyyah Kota Kediri. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan jenis studi kasus dan teknik analisa data Miles and Huberman. Hasil penelitian menunjukkan bahwa (1) teknik pembelajaran membaca al-Quran menggunakan teknik membaca secara terus menerus atau drilling dan pembiasaan; (2) Teknik ini terbukti efektif dan efisien yang didasarkan pada teori Ivan Pavlov dan Teori Habitus Pierre S. Bourdeun; (3) Hal ini terlihat pada adanya peningkatan prosentase kompetensi siswa dalam membaca al Quran dari 55 menjadi 93 persen serta manpu mencapai target pembelajaran, yakni mampu membaca al-Quran sesuai tajwid yang ada; (5) Hasil lain yang didapat dari teknik ini berupa siswa mampu menghafal surat-surat pendek dalam juz amma, mulai dari an-Nas hingga al-Qariah, Asmaul Husna dan bacaan dzikir setelah sholat. Kondisi inimerupakan capaian yang sangat baik mengingat 90 persen input siswa baru MI al-Irsyad al-Islamiyah belum memiliki kompetensi itu.